Epidemiology and factors associated with amoebic liver abscess at a tertiary care hospital in Northern India (Panacea Journal of Medical Sciences, 2024)
Introduction: Liver abscess is a collection of purulent material in the liver most commonly seen in the tropical countries. It can sometimes lead to significant morbidity and mortality if not treated timely and adequately. Through this study we wish to put light upon the current status of clinical aspects, laboratory features, and outcomes of liver abscess.Materials and Methods: The study was conducted at a tertiary care hospital in Northern India in the period of August 2020 to July 2021. All patients diagnosed with liver abscess of size >5 cm or left lobe liver abscess of any size were included in the study. All relevant laboratory investigations were conducted. The outcomes were noted and data was entered in MS Excel sheet. Analysis was done using SPSS version 26.Results: Sixty-three patients were included in the study. A male predominance was noted. Mean age at presentation was 37.8 years. Most patients were part of the lower socioeconomic class. Pain abdomen and fever were the most common presenting symptoms. Amoebic liver abscess was much more frequently seen than pyogenic liver abscess. Deranged coagulation profile was seen in 88.9% patients. 85.7% patients were amenable to treatment with minimal intervention. Mortality as an outcome was seen in 9.5% patientsConclusion: Significant correlation was found between various laboratory parameters and outcomes such as length of hospital stay and mortality. Early diagnosis and treatment is crucial in management of patients with liver abscess even today.